The IASB`s Project of New Standard for Leases - Nemcová, Lenka (2015)
The work aims to analyze the new leasing standard which is supposed to be adopted by IFRS as well as US GAAP. The new standard represents one of the steps in the process of harmonization and convergence between two predominant world accounting standards, which has been in progress since the year 2002. The work provides readers with the comparison of these two leasing standards, resulted from which the need of common lease standard arose. This led to the first exposure draft of convergence standard issue, and finally the re-exposure draft issue. Because the new accounting standard is still in progress, I provide the analysis of the process as at the end of August.